Dual Lipases System In Transesterification Of Ethyl Ferulate With Olive Oil: Optimization By Response Surface Methodology - Nurul Jannah Abd Rahman; Salina Mat Radzi; Hanina Mohd Noor (Asian Journal of Applied Sciences (AJAS), 2024)
Non-Indexed Publication